2012
DOI: 10.1590/s0074-02762012000900003
|View full text |Cite
|
Sign up to set email alerts
|

Hansen's disease: a vanishing disease?

Abstract: The introduction, implementation, successes and failures of multidrug therapy (MDT) in all Hansen's disease endemic countries are discussed in this paper. The high efficacy of leprosy treatment with MDT and the global reduction of prevalence led the World Health Organization, in 1991, to establish the goal of elimination of Hansen's disease (less than 1 patient per 10,000 inhabitants) to be accomplished by the year 2000. Brazil, Nepal and East Timor are among the few countries that didn't reach the elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
11
0
4
Order By: Relevance
“…In Brazil, major changes in attention to public health that occurred from 2007-2010, as investment in primary care-oriented decentralized health, the encouragement in the control of disease in children under 15 years old and contacts monitoring, were important strategies to reach the goal of leprosy control [17]. These changes corroborate the number of overall cases, and in children under 15 years old, found by this study.…”
Section: Discussionsupporting
confidence: 84%
“…In Brazil, major changes in attention to public health that occurred from 2007-2010, as investment in primary care-oriented decentralized health, the encouragement in the control of disease in children under 15 years old and contacts monitoring, were important strategies to reach the goal of leprosy control [17]. These changes corroborate the number of overall cases, and in children under 15 years old, found by this study.…”
Section: Discussionsupporting
confidence: 84%
“…According to the study, the detection coefficient of cases homogeneously dropped worldwide from 1999, with the exception of only eight countries, among which Brazil is not included (6) . The authors (13) stated that the slow reduction in the incidence of the disease in endemic countries such as Brazil, India and Indonesia, reflects the epidemiological characteristics of M. Leprae due to its long incubation period. This study Source: Secondary data -Sinan, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological study identified risk groups and factors that contribute to disease control and provide the Brazilian ministry of health with a scientific basis for political and administrative actions and investments in government resources (13) . It is assumed, therefore, that the de- tection indicators are dropping as a result of government disease control and eradication actions.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, the disease is challenging to diagnose since there is no gold-standard method to differentiate between infection and disease. Leprosy is also a neglected disease, being endemic in developing countries, where detection rates show only a slight trend toward a decrease in disease (or number of cases) in spite of good treatment and the efforts of the World Health Organization (WHO) to improve the quality of leprosy control programs [1]. It is accepted that transmission occurs from human to human through the upper airways, although intermediate hosts like armadillos may play a role in certain places, such as the United States [2].…”
Section: Introductionmentioning
confidence: 99%